Effects of device-assisted practice of activities of daily living in a close-to-normal pattern on upper extremity motor recovery in individuals with moderate to severe stroke: study protocol of a randomized control trial - Justin M. Drogos; Carolina Carmona; Riegele Arceo; Jun Yao (Trials)
Abstract Background The majority of individuals with chronic stroke have residual upper extremity (UE) disability which they cite as their greatest barrier to recovery. Using orthoses, robotic devices, and functional electrical stimulation (FES) represent rehabilitation techniques that have demonstrated the ability to improve arm and hand function in the chronic stroke population, but individuals with more severe impairments are typically not eligible for these studies. The very few studies incorporating these techniques with the severely impaired population do not utilize volitional FES control or modulated loading, which has been shown to promote greater motor recovery and functional improvement. An UE intervention utilizing an advanced orthosis incorporating volitionally controlled FES and robotically modulated shoulder abduction (SABD) loading may provide a pathway to improved coordinated use of the arm and hand for the more severely impaired chronic stroke population. Methods In a double-blinded, two-baseline, randomized control trial individuals with chronic moderate to severe stroke resulting in UE hemiparesis will participate in a task-based reaching-grasping-retrieving-releasing (GR3) intervention three times a week for 8 weeks. An anticipated 60 individuals will perform a repeated GR3 task with the ReIn-Hand device (ReIn-Hand), a customized forearm/hand orthosis integrating volitionally controlled FES, to assist with paretic hand-opening. Participants will be randomly assigned to a control group (ReIn-Hand only) or experimental group which will also receive modulated SABD loading via the PACT3D robot. Groups will be compared by (1) their change in function primarily measured by the Box and Blocks Test; (2) change in performance measured by kinematic analysis of reaching and hand-opening and (3) changes in neural motor recovery measured using electroencephalography (EEG) and magnetic resonance imaging (MRI). Discussion The present study will evaluate the effectiveness of a novel interventional device, with and without shoulder abduction assistance, as part of a task-specific training protocol with the moderate to severe chronic stroke population. The focus on the more impaired chronic stroke population provides the opportunity to improve the rehabilitation of this overlooked population. Functional and structural measures using advanced imaging techniques offer the possibility to further delineate recovery and compensation at the neuronal level. Trial registration ClinicalTrials.gov ID NCT04077073. Registration date: September 04, 2019.